Trends in technology interventions for geometry learning in elementary schools - Zainal, Zaid; Krismanto, Wawan (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purposes: The use of technology is one of the alternative strategies recommended as a cognitive intervention and has the potential to optimize geometry learning when designed and implemented based on relevant theory. However, there is still a gap, namely the limited of reviews in the last decade that specifically address these technological trends for elementary school. This literature review aims to uncover these technological trends, their contributions, and a map of learning domains that could be improved.Method: This study used a systematic literature review method. A total of 57 articles on the use of technology in geometry learning in elementary schools were reviewed and analyzed. The articles were obtained from journal publishers and proceedings indexed by Scopus. The research procedure was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA).Findings: The results show that various technologies have been utilized in geometry learning in elementary schools, with Augmented Reality, GeoGebra, SketchUp, Minecraft, and 2D and 3D models being the most researched technologies. Research trends show a shift in the role of technology from merely a visual tool to a contextual, adaptive, and immersive learning ecosystem, demonstrated by the increasing use of technology. Geometry conceptual knowledge and spatial skills were the most dominant and consistently researched learning domains. For students, technology facilitate their geometry learning and potentially enhance their cognitive and affective abilities. For teachers, technology is both an effort of improving their pedagogical practices, including transforming geometry learning.Significance: Mapping the contribution of research results reinforces the importance of using technology in geometry learning, as it has the potential to optimize various learning domains. Finally, this study identifies remaining research gaps and outlines the potential for future research important to geometry learning in elementary schools.